The relationship between dating, love and social anxiety problems among the secondary school students - Yahaya, Azizi; Suari, Asiah (2010)
The aim of this study is to identify the emergence of dating phenomenon, love affair and their relationship with social anxiety amongst the students in secondary schools. Two hundred and forty students were chosen from eight different schools in Johor Bahru district for this study. The cluster on cluster sampling technique was applied and questionnaires on dating, love affair, sex and social anxiety for adolescents were used in this study. The alpha croncbach for both items are 0.7207 and 0.9690 accordingly. The results from the study have shown that the students perceptions towards love affair and social anxiety problem are at moderate levels while the most dominant love style among the students is ‘pragmatic love style’. There are significant differences between students who involve in dating in relation to races and standard of living, sex in relation to gender and love affair in relation to races. On the other hand, there are no significant differences among the other factors being studied such as sex and social anxiety in relation to races and in between love affair, dating, sex and social anxiety in relation to the location of their hometown.